Does Protocol Matter for Repetition Volume? A Meta-Analytic Investigation of Volitional Failure Versus the Traditionally Used 75-Repetition Blood Flow Restriction Resistance Training - Nicholas Rolnick; Victor S. de Queiros; Ethan C. Hill; Thomas Bjørnsen; Tim Werner; Jeremy P. Loenneke (Sports Medicine - Open)
Abstract Background It is recommended to prescribe sets to volitional muscular failure (e.g., 4 sets) or a fixed repetition scheme of 75 repetitions (1 × 30, 3 × 15) in low-load resistance exercise with blood flow restriction (BFR-RE). While prior studies suggest both protocols may elicit similar muscular adaptations, the extent to which this is explained by matched exercise volume remains unclear. Objectives This systematic review and meta-analysis evaluated the number of repetitions performed during four sets of low-load BFR-RE to volitional muscular failure and compared these with the fixed 75-repetition scheme. The goal was to determine whether the two protocols yield similar total and per-set repetition volumes. Methods On 10/31/2024, two databases (PubMed® and Scopus) were used to identify studies that applied a protocol of four sets to volitional muscular failure in BFR-RE with a load of ≤ 50% of one repetition maximum (1RM), regardless of the outcome investigated. Mean repetition data were pooled using a random-effects meta-analysis. One-sample t-tests compared per-set and total volumes to the reference scheme (1 × 30, 3 × 15). Results Across 25 studies (47 means; n = 678), the estimated total repetitions performed to failure was 73.1 (95% CI: 61.1 to 85.2). Per-set means were 36.0 (95% CI: 30.5 to 41.4), 14.7 (95% CI: 12.2 to 17.1), 11.5 (95% CI: 9.2 to 13.8), and 10.4 repetitions (95% CI: 8.1 to 12.7) for sets 1 through 4, respectively. Conclusion Four sets of BFR-RE to volitional muscular failure produce similar total repetition volume compared to the commonly implemented fixed 75-repetition scheme, though the distribution of repetitions per set differs. These findings provide insight into the mechanical equivalence of two widely used BFR-RE prescriptions.